Validation of emotional stimuli flashcards for conducting ‘response to reward’ fMRI study among Malaysian undergraduates - Nisha Syed Nasser,; Hamed Sharifat,; Aida Abdul Rashid,; Suzana Ab Hamid,; Ezamin Abdul Rahim,; Mazlyfarina Mohamad,; Tyagi, Rohit; Siti Irma Fadhilah Ismail,; Ching, Siew Mooi; Subapriya Suppiah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Problematic Instagram Use (PIGU) is a specific Internet addiction disorder observed among the youth of today. Functional magnetic resonance imaging (fMRI) can objectively assess regional brain activation in response to addictionspecific rewards, e.g. viewing picture flashcards. Pictures that were uploaded onto Instagram by users with PIGU issue have often been associated with risky behaviors in their efforts to gain more ‘Likes’. Thus, it was hypothesized that individuals with PIGU issue are more drawn to negative emotional cues. To date, no literature on addiction-specific cues found on the local database. The objective of this study was to conduct an out-of-scanner validation study to create a database of pictures with negative emotional cues that evoke responses of arousal among individuals with PIGU issue. Forty-four Malaysian undergraduates (20 undergraduates in the PIGU group, 24 undergraduates in the control group) were randomly recruited as the subjects in the present study. They were grouped into PIGU or control groups based on the evaluation using the Smartphone-Addiction-Scale-Malay version (SAS-M) and modified Instagram Addiction Test (IGAT) and whether they fulfilled the definition of addiction according to Lin et al. (2016). They were administered with 200 content-specific pictures that were multidimensional, i.e. arousal (excitation or relaxation effects), approachavoidance (motivational direction) and emotional valence (positive or negative feelings) to describe their perceptions on the psychological properties of the pictures using a 9-point Likert scale. The results showed that the subjects with PIGU issue, who viewed the negative emotional cues, demonstrated significant positive correlations between arousal and valence (z = 4.834, p < .001, effect size = 0.69) and arousal and avoidance-approach (z = 4.625, p < .001, effect size = 0.66) as compared to the controls and were more frequently aroused by negative emotional type of stimuli. As a conclusion, a database of validated, addiction-specific pictures can be developed to potentiate any future cue-induced response to reward fMRI studies for assessing PIGU.